Evaluation of plant and animal tea solution fertilizers on the soil fertility and growth of locust bean (Parkia clappertonia) seedlings in the nursery - E. I., Moyin Jesu (Universiti Putra Malaysia Press, 2003)
An experiment was carried out at Akure in the rainforest zone of Nigeria to determine the effectiveness of liquid plant and animal tea solutions as fertilizers on the growth of two cr&/JS of locust bean (Parkia clappertonia) tree seedlings in the nursery. Eight manurial tea solutions were used namely; coffee, cocoa, Cajanus-eajan (Pigeon pea), Cashew, plantain leaf tea fertilizers, goat dung, turkey and duckmanure tea fertilizers, applied at 100 mL/ 10 kg soil filled polybag with NPK 15-15-15 at 1 g NPK/10 kg soil and control (no manure, no fertilizer). They were replicated three times and arranged in a completely randomized design. The soil and manurial tea fertilizers were chemically analysed before planting locust bean seeds. The results showed that the manurial tea solutions increased the plant height, stem girth, number of leaves and number of branches, shoot weight and root length at harvest, leaf chemical composition of locust bean seedlings and the soil nutrient status significantly (P < 0.05). For soil chemical composition, coffee leaf solution increased the soil pH, a.M, N,P,K, Ca and Mg by 4.2%, 10%, 13.6%,58.3%,22%, 91.3% and 84% respectively when compared with cajanus leafsolution while the cashew leaf solution increased the soil pH, a.M, N, P,K, Ca and Mg by 2.8%, 11 %, 48%, 57%, 8.3%, 38.5% and 33% when compared with cocoa leaf solution respectively. Coffee leaf tea solution increased the soil pH, a.M, N, P, K, Ca and Mg by 24%, 74%, 82%, 89%, 96%, 98% and 97% compared with the control treatment respectively. Coffee tea solution increased the soil pH, a.M, K, Ca and Mg by 25%, 69%, 39%, 98.7% and 99% compared to NPK fertilizer treatment respectively. Turkey manure tea solution also increased the soil pH, a.M, N, P and Mg by 2%, 19%, 37%, 42% and 82% respectively compared to the duck manure tea. Concerning the growth parameters of locust bean seedlings, Cashew leaf tea solution increased the plant height, number of leaves, number of branches, stem girth, root length and shoot weight by 33%, 41 %, 33.3%, 12.2%, 36.4% and 16% compared to the NPK fertilizer treatment respectively. It also increased the same growth parameters by 61 %, 71 %, 78%, 62%, 77% and 71 % respectively when compared to the control treatment. In the locust bean leaf chemical composition, the cashew leaf tea solution increased the leaf N, P, K, Ca and Mg by 42%, 45%, 4.16%, 85% and 83% when compared with NPKfertilizer respectively. Cashew leaf solution and turkey manure tea solutions increased the growth, leaf and soils of locust bean seedlings most.